MDM2 inhibitors, nutlin-3a and navtemadelin, retain efficacy in human and mouse cancer cells cultured in hypoxia - Lerma Clavero, Ada; Boqvist, Paula Lafqvist; Ingelshed, Katrine; Bosdotter, Cecilia; Sedimbi, Saikiran; Jiang, Long; Wermeling, Fredrik; Vojtesek, Borivoj; Lane, David P; Kannan, Pavitra (Scientific reports, 2023)
Activation of p53 by small molecule MDM2 inhibitors can induce cell cycle arrest or death in p53 wildtype cancer cells. However, cancer cells exposed to hypoxia can develop resistance to other small molecules, such as chemotherapies, that activate p53. Here, we evaluated whether hypoxia could render cancer cells insensitive to two MDM2 inhibitors with different potencies, nutlin-3a and navtemadlin. Inhibitor efficacy and potency were evaluated under short-term hypoxic conditions in human and mouse cancer cells expressing different p53 genotypes (wild-type, mutant, or null). Treatment of wild-type p53 cancer cells with MDM2 inhibitors reduced cell growth by > 75% in hypoxia through activation of the p53-p21 signaling pathway; no inhibitor-induced growth reduction was observed in hypoxic mutant or null p53 cells except at very high concentrations. The concentration of inhibitors needed to induce the maximal p53 response was not significantly different in hypoxia compared to normoxia. However, inhibitor efficacy varied by species and by cell line, with stronger effects at lower concentrations observed in human cell lines than in mouse cell lines grown as 2D and 3D cultures. Together, these results indicate that MDM2 inhibitors retain efficacy in hypoxia, suggesting they could be useful for targeting acutely hypoxic cancer cells.
Keywords: Animals; Tumor Suppressor Protein p53; apoptóza; Hypoxia; Cell Line, Tumor; protoonkogenní proteiny c-mdm2; Apoptosis; Neoplasms; nádory; lidé; Mice; Antineoplastic Agents; protinádorové látky; myši; hypoxie; Proto-Oncogene Proteins c-mdm2; nádorový supresorový protein p53; zvířata; nádorové buněčné linie; Humans